COMPUTATION OF RAIN-INDUCED ATTENUATION AT CENTIMETRIC WAVE BAND FOR SLANT PATH COMMUNICATION IN NORTH CENTRAL NIGERIA - K.C. Igwe; O.D. Oyedum; J.S. Ojo; O.O. Obiyemi; A.G. Ibrahim (Malaysian Journal of Science, 2024)
In this paper, five globally recognised rain attenuation models for slant path communication are considered in order to compute the amount of attenuation and obtain the optimal rain attenuation models for North Central region of Nigeria. The models are Bryant, Garcia-Lopez, ITU-R P.618-9, Simple Attenuation and Svjatogor. These models were evaluated at Ku and Ka-bands and at three elevation angles of 55o, 42.5o and 23o. 5-minute integration time rainfall data obtained from the Tropospheric Data Acquisition Network (TRODAN), Anyigba, Nigeria was converted to 1-minute integration time using Lavergnat and Gole rain rate model. Predictions were made for circularly polarised signals at different percentages of time of the year. The cumulative distribution of rain attenuation computed showed that attenuation values generally ranged between 9 and 19 dB at time percentage exceedance of 0.01% for the Ku-band, while it ranged between 21 and 41 dB at 0.01% for the Ka-band. Also, computations by the Garcia-Lopez and Bryant models were in agreement with the ITU-R P.618-9 model, while the Simple Attenuation and Svjatogor models underestimated the computed rain attenuation values at every percentage of time in all the stations considered.